Transformasi Sosial dan Spiritualitas: Analisis Tren Kajian Keagamaan di Kalangan Perempuan Metropolitan melalui Perspektif Sosiologi Agama Emile Durkheim - Sarah Sakhowah (Advances In Education Journal, 2025)
The trend of religious study groups among metropolitan women represents a socio-religious phenomenon that has increasingly strengthened within modern urban life. This study aims to analyze the meanings and functions of religious study activities for metropolitan women through the perspective of Emile Durkheim’s sociology of religion. This research employs a descriptive qualitative approach using in-depth interviews with seven women who actively participate in religious study groups. The findings indicate that the majority of participants experience increased inner peace, improved quality of worship, and the formation of supportive social relationships. From Durkheim’s perspective, religious study activities function as collective rituals that reinforce collective consciousness, social solidarity, and prevent alienation amid the pressures of metropolitan life. These findings affirm that religious study groups play a strategic role in maintaining the spiritual and social balance of urban women.